2020
DOI: 10.1186/s12915-020-00881-6
|View full text |Cite
|
Sign up to set email alerts
|

Genomic evidence for recurrent genetic admixture during the domestication of Mediterranean olive trees (Olea europaea L.)

Abstract: Background Olive tree (Olea europaea L. subsp. europaea, Oleaceae) has been the most emblematic perennial crop for Mediterranean countries since its domestication around 6000 years ago in the Levant. Two taxonomic varieties are currently recognized: cultivated (var. europaea) and wild (var. sylvestris) trees. However, it remains unclear whether olive cultivars derive from a single initial domestication event followed by secondary diversification, or whether cultivated lineages are the result of more than a sin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
70
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(81 citation statements)
references
References 102 publications
(116 reference statements)
9
70
2
Order By: Relevance
“…Genomics refers to the genome-wide approaches dealing with the structure, function, evolution, mapping and editing of genomes. Olive's genome size is~1.4 Gb and is characterized as a medium-sized plant genome [13,14]. Due to the evidence that a large fraction of the genome derived by tandem repeats amplification and Long Terminal Repeats-retrotransposons (LTR-Res) in combination with the high level of heterozygosity, the olive genome assembly at chromosome-level scaffolds is a relatively difficult task [3].…”
Section: Advances In Olive Genome Assembly and Annotation And Its Significance In Population Genetic Studiesmentioning
confidence: 99%
“…Genomics refers to the genome-wide approaches dealing with the structure, function, evolution, mapping and editing of genomes. Olive's genome size is~1.4 Gb and is characterized as a medium-sized plant genome [13,14]. Due to the evidence that a large fraction of the genome derived by tandem repeats amplification and Long Terminal Repeats-retrotransposons (LTR-Res) in combination with the high level of heterozygosity, the olive genome assembly at chromosome-level scaffolds is a relatively difficult task [3].…”
Section: Advances In Olive Genome Assembly and Annotation And Its Significance In Population Genetic Studiesmentioning
confidence: 99%
“…Additionally, southern Mediterranean countries are expected to be the most afflicted by heatwaves and drought, and a huge backlash on agriculture productivity is predictable [ 18 , 19 ]. Olea europaea L. is one of the oldest permanent crops of the Mediterranean, where it has an essential socioeconomic and ecological relevance [ 19 , 20 , 21 , 22 , 23 , 24 ]. Nearly all (95%) of global olive oil demand is satisfied by the southern European countries; among them, Spain is the most devoted to oil production, followed by Italy, Greece and Portugal [ 23 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, olive is a recalcitrant species to in vitro manipulation [ 14 ]; however, in the last two decades, a small number of studies reported the development of olive genetic transformation protocols, which have been used for obtaining transgenic plants expressing reporter genes and even transgenes of interest, although in most cases transformed explants were of juvenile origin. The importance of this technology will increase in the near future with the advancement in the olive genome sequence projects that are currently underway [ 15 , 16 , 17 ], which could allow the identification of genes of interest for future breeding programs. In addition, protocols for the regeneration of somatic embryos (SE)from explants of adult origin are needed to develop new cultivars or rootstocks useful for breeders.…”
Section: Introductionmentioning
confidence: 99%